Forensic Investigation of Drug and Food Crimes in Digital Marketplace - Meutia, Adinda; Luthfi, Ahmad (Journal of Information System and Informatics, 2025)
This research holds great significance as it is anticipated to safeguard customers from harmful frug and food products in cyberspace and to enforce the law by offering solid evidence to bring criminals to justice. Furthermore, this research helps to better understand how crimes that take place in the marketplace are committed, which enables the implementation of more effective preventive measures. Besides, in order to combat cybercrime, the findings of this study may serve as the foundation for the creation of more effective digital forensic investigation techniques. In order to perform digital forensic investigations of drug and food offenses using the marketplace, this study aims to develop an efficient and successful model or implementation guideline. This seeks to methodically direct the inquiry process while adhering to relevant norms. The objective of this research endeavor is to provide a model or practical guideline that is both effective and efficient for using the marketplace to undertake digital forensic investigations of drug and food crimes. This seeks to methodically direct the research process while adhering to relevant criteria. The following stages make up the Design Science Research (DSR) method of research: The issue in this project is "How to conduct a digital forensic investigation for Drug and Food crimes using the marketplace so that it can be used as evidence in court?" Then, in order to adopt answers from related research and make adjustments linked to research difficulties, a literature review is conducted to locate prior research. A model or implementation guideline for performing digital forensic investigations of the marketplace is the type of solution or artifact anticipated in this project. The next phase is solution design, which involves using an existing forensic investigation framework to create an artifact design. Following every step of the framework, case study experiments are then conducted to test the artifact design. The examination of the artifact design by both experts and consumers is the last phase.